2012
DOI: 10.1007/s12033-012-9517-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of Drought Tolerance in Tea by cDNA-AFLP Based Transcript Profiling

Abstract: A cDNA-AFLP approach was used to identify transcript and/or genes specifically expressed in response to drought in tea. Drought was artificially induced and whole genome transcript profiling was done at three different stages-6 days before wilting, 3 days before wilting and at wilting stage of both tolerant and susceptible cultivars, and genetic differences was thus visualized as polymorphisms in the transcriptome. The cDNA-AFLP technique allowed genes and transcripts to be identified in the tolerant genotype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 43 publications
0
11
0
1
Order By: Relevance
“…DS signal perception and transduction by plants cells induced the expression of regulatory and functional sets of genes (Gupta et al, 2012(Gupta et al, , 2013. By comparing the expression of five droughtrelated genes in cultivars during the different phases of DS, we found that the expression levels of five genes were differentially up-regulated under DS.…”
Section: Gene Expression Differences Among the Tea Cultivars Under Drmentioning
confidence: 88%
See 1 more Smart Citation
“…DS signal perception and transduction by plants cells induced the expression of regulatory and functional sets of genes (Gupta et al, 2012(Gupta et al, , 2013. By comparing the expression of five droughtrelated genes in cultivars during the different phases of DS, we found that the expression levels of five genes were differentially up-regulated under DS.…”
Section: Gene Expression Differences Among the Tea Cultivars Under Drmentioning
confidence: 88%
“…However, few studies have focused on changes to the phytohormone content in tea plants experiencing DS; interaction of osmolytes, antioxidases and phytohormones in tea plants are not well understood under DS and rewatering. Furthermore, a set of drought responsive genes and their pattern of expression were identified by using cDNA-amplified fragment length polymorphism (cDNA-AFLP) and suppression subtractive hybridization (SSH) (Gupta et al, 2012(Gupta et al, , 2013. Nevertheless, during and after DS, comprehensive physiological and molecular studies on the responses of susceptible and tolerant mature field-grown tea cultivars are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Growth and productivity of tea plants largely depends on their capacity to adapt to abiotic stress, namely temperature, drought, metal, and nutritional disturbances. Although the effects of some individual environmental factors on the tea plant are well documented (Handique and Manivel, 1990;Chakraborty et al, 2002;Panda et al, 2003;Upadhyaya and Panda, 2004a;Jeyaramraja et al, 2005;Sharma and Kumar, 2005;Cheruiyot et al, 2007;Cheruiyot et al, 2008;Upadhyaya et al, 2008;Yadavand Mohanpuria, 2009;Upadhyaya et al, 2011;Upadhyaya et al, 2012;Das et al, 2012;Gupta et al, 2012), the effects of interacting abiotic factors remain poorly investigated.Therefore, the objective of this review is to highlight the effects of drought, heavy metal stress, and their interaction on growth, water relationships, nutrient status, and antioxidative responses during abiotic stress and its recovery in the tea plant.…”
Section: Introductionmentioning
confidence: 99%
“…Tea is cultivated in more than 2.71 million ha across 34 countries in Asia, Latin America, Oceania, and Africa, sustaining their national economies (Deka et al 2006;Barua 1994;Wilson and Clifford 1992a, b). Among the many biotic and abiotic factors that confront tea production (Gupta et al 2013;Das et al 2012;Hazarika et al 2009), infestation by insect and mite pests (arthropods) are the most economic, causing on average a 5 to 55 % yield loss (Muraleedharan 1992;Wilson and Clifford 1992a, b) amounting to approximately US$500 million to $1 billion (Jain 1999). Interestingly, recent research by our group showed that jassids (hemipteran) influence tea quality (Gohain et al 2012).…”
Section: Introductionmentioning
confidence: 99%